Phytochemical composition and bioactivities of Crataegus aronia as antioxidant, antibacterial and antioxidative stress in red blood cells – Is it a window of hope for children with glucose-6-phosphate dehydrogenase deficiency - Ghassab M. Al-Mazaideh; Ahmed H. Al-Mustafa; Sulaiman Mohammed A. Alnasser; Ibrahim Nassir-Allah; Khaled A. Tarawneh; Fuad Al-Rimawi; Mohamad Nasir Mohamad Ibrahim; Mohammed Ayed Huneif; Shifaa O. Alshammari; Asim Ali Yaqoob; Fadel Wedian; Mohammed Helmy Faris Shalayel (Heliyon, 2022)
Background: Crataegus aronia (C. aronia) extracts have been used medicinally since ancient times and are often utilized in traditional Arab medicine. An extensive study has revealed that Crataegus species have antioxidant, antibacterial, anti-inflammatory, and hypotensive properties. Objectives: This work was performed to explore the phytochemical contents of C. aronia extract, as well as its antioxidant and antibacterial properties, and to assess the lipid peroxidation level as an oxidative stress biomarker in erythrocytes. Methods: Chemical constituents in the methanolic extract of C. aronia were identified by gas chromatography-mass spectrometry and their relative concentrations were determined. The antioxidant activity of C. aronia extract was determined using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. The effect of C. aronia on the concentration of malondialdehyde (MDA) in the erythrocyte hemolysates was studied. Also, the crude extract was assessed for its antimicrobial activity through agar diffusion and microbroth dilution assays. Key findings: The DPPH IC50 value of the extract showed that the antioxidants activity was equal to (14.3 μg/mL) and according to FRAP assay, the antioxidant activity was in the range of 33.9 μmol–82.86 μmol Fe+2/g dw. The extract exerts a protective effect against oxidative stress in RBCs and shows a 50% inhibition of malonyldialdehyde (MDA) at 39.48 μg/mL extract. Minimum inhibitory concentrations were found in the range of 800–1000 μg/mL of leave extracts. The phytochemical analysis showed that the total phenols, flavonoids, and flavonols content were 494.071 mg GAE/g extract, 155.251 mg RE/g extract, and 103.2049 mg RE/g extract). C. aronia extract contains alkaloids, flavonoids, terpenoids, and steroids. Crude extract of C. aronia was more potent in inhibiting the growth of B. subtilis, S. aureus and M. luteus with MIC and MBC values of 800,800 and 1000 μg/mL, respectively. According to GC-MS, 20 compounds were identified: dihydro-3-methylene-5-methyl-2-furanone (14.71%), hexanoic acid (6.57%), ethyl 3,5-ditert-butyl-4-hydroxybenzoate (6.4%), N, N-dimethylheptadecan-1-amine (4.91%), methyl 2-oxobutanoate (4.14%), glyceraldehyde (3.98%), and 2-methoxy-1-(2-nitroethenyl)-3-phenylmethoxybenzene (3.16%), were the major constituents. Conclusion: This study may open a window of hope for children with Glucose-6-phosphate dehydrogenase disorder by possible utilization of the active ingredients of C. aronia to minimize both oxidative stress and infection which negatively impact the disease sequelae.According to these in vitro experiments, this plant extract has a significant amount of natural antioxidants, which may aid in the protection of various oxidative stresses. As a result, employing the active components of C. aronia to minimize oxidative stress and infection, both of which have a detrimental impact on disease sequelae, may bring hope to children with Glucose-6-phosphate dehydrogenase disorder.